2013
DOI: 10.1371/journal.pone.0061118
|View full text |Cite
|
Sign up to set email alerts
|

Prion Protein Gene Variability in Spanish Goats. Inference through Susceptibility to Classical Scrapie Strains and Pathogenic Distribution of Peripheral PrPsc

Abstract: Classical scrapie is a neurological disorder of the central nervous system (CNS) characterized by the accumulation of an abnormal, partially protease resistant prion protein (PrPsc) in the CNS and in some peripheral tissues in domestic small ruminants. Whereas the pathological changes and genetic susceptibility of ovine scrapie are well known, caprine scrapie has been less well studied. We report here a pathological study of 13 scrapie-affected goats diagnosed in Spain during the last 9 years. We used immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 51 publications
3
34
0
1
Order By: Relevance
“…Since Q 222 -Tg501 mice and K 222 -Tg516 mice express exactly the same PrP C sequence, except for the Q/K 222 amino acid substitution, and have similar PrP C expression levels, we can assume that the lack of transmission efficiency of classical scrapie is linked to the K 222 amino acid. This conclusion is consistent with the results reported in the accompanying article by Lacroux et al (27) and previous epidemiological studies carried out in different European goat scrapie outbreaks where the K 222 -PrP C variant was detected only in healthy goats (12,15,23,24). Taken together, these results suggest that the K 222 variant of goat PrP C is strongly resistant to a wide range of classical scrapie strains.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Since Q 222 -Tg501 mice and K 222 -Tg516 mice express exactly the same PrP C sequence, except for the Q/K 222 amino acid substitution, and have similar PrP C expression levels, we can assume that the lack of transmission efficiency of classical scrapie is linked to the K 222 amino acid. This conclusion is consistent with the results reported in the accompanying article by Lacroux et al (27) and previous epidemiological studies carried out in different European goat scrapie outbreaks where the K 222 -PrP C variant was detected only in healthy goats (12,15,23,24). Taken together, these results suggest that the K 222 variant of goat PrP C is strongly resistant to a wide range of classical scrapie strains.…”
Section: Discussionsupporting
confidence: 93%
“…In goats, half a hundred polymorphisms in the open reading frame (ORF) of the prnp gene have been described (10)(11)(12), including some silent mutations, a three-octapeptide-repeat variant (13), and a nonsense mutation at codon 32 (14). Although several polymorphisms are shared by sheep and goats, to date, only some correlations between some variants of goat PrP C (goPrP C ) and susceptibility to TSE have been published.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Mexican goats, allelic variants F/L 201 in linkage with P/S 240 were found, in addition to P/Q 168 , which has also been described in Italian, Greek and Cypriot goats (Goldmann et al, 2011). A recent study identified five new polymorphisms of the PRNP that lead to amino acid changes (G/D 74 , M/T 112 , R/S 139 , L/F 141 and Q/R 215 ) and a new silent mutation at codon 122 in Spanish goats (Acín et al, 2013). Kipanyula et al (2014) described two additional new polymorphisms in Small East African and Norwegian white goats, A/V 116 and Q/L220, respectively.…”
Section: Role Of Prnp In Small Ruminantsmentioning
confidence: 65%
“…Similarly to sheep, the caprine Prnp gene is highly polymorphic. 6,[9][10][11][12][13][14][15][16] Field studies, conducted in different countries on a variety of goat breeds, assigned some degree of protection against scrapie to the following alleles Met-142, Arg-143, Asp-146, Ser-146, His-154, Gln-211 and Lys-222. 11,13,14,[17][18][19][20][21][22][23] Among these, Met-142 is linked to prolonged incubation period, 13,17,21,23 while Arg-143 18 and His-154 14,18,19,21,23 are associated with moderate protection.…”
Section: Introductionmentioning
confidence: 99%